Analisis Risiko Kegagalan Proses Produksi Bakpia Menggunakan Metode FMEA Di Rumah Produksi Bakpia AS Sidoarjo - Isa Abdussalam; Dwi Sukma Donoriyanto Dwi Sukma Donoriyanto (Fakultas Teknik Universitas Ibnu Sina, 2024)
The bakpia production process, which consists of various stages, starting from selecting raw materials, mixing dough, baking, to packaging, has the potential risk of failure at each stage. These risks, if not managed properly, can reduce product quality, reduce customer satisfaction, and even cause business losses. The method used in the study was FMEA and proposed improvements with 5W + 1H. Based on the FMEA analysis, the risk with the highest Risk Priority Number (RPN) value was incorrect temperature settings (240). The 5W + 1H analysis revealed the main causes of this risk, namely uncalibrated ovens, uneven heat distribution, and lack of temperature monitoring during baking, which was carried out in the production area by workers. To reduce the risk, periodic oven calibration, use of temperature monitoring devices, worker training, and standardization of operational procedures are recommended. This study proves that the combination of FMEA and 5W + 1H methods is effective in helping MSMEs such as Bakpia AS in identifying, analyzing, and mitigating risks in order to improve product quality and operational efficiency